Kajian Mutu Ikan Kayu Bubuk Yang Dikemas Plastik Dengan Nitrogen Dan Tanpa Nitrogen - Enembe, Pinini; Makapedua, Daisy Monika; Sanger, Grace; Kaseger, Bertie Elias; Harikedua, Silvana D; Damongilala, Lena Jeane (Sam Ratulangi University, 2020)
Fish is one of the food items that become famous of the capture fisheries sector such as Skipjack fish. However, fish is categorized as perishable food therefore efforts are needed to inhibit the spoilage process by preserving and processing the fish. One of traditional Japanese fish product is Katsuo-bushi or smoked fish which processed by low temperature smoking in many hours.The purpose of this study is to study the quality and shelf life of katsuo-bushi flakes (hana-katsuo) that is packed in plastic with nitrogen and without nitrogen The methods used were organoleptic test, water content and Total Place Count (TPC), and the storage period for 0 day, 7 days and 14 days. The results showed that the organoleptic test for appearance, smell and texture with an average value of 7 which complies Indonesia national standard (SNI). Based on the water content showed that hanakatsuo which packed with plastic in nitrogen and without nitrogen have increased water content at a shelf life of 0, 7 and 14 days with the highest value with a value of 13.15%, the product still complies the SNI standards. Furthermore, the results of TPC showed that hana-katsuo which is packed in plastic with nitrogen does not complies the SNI, whereas hana-katsuo which is packed in plastic without nitrogen on day 0 is too little to count while on day 7 and 14 it does not comply the SNI.Ikan adalah salah satu bahan pangan yang banyak dicari orang sehingga ikan menjadi primadona sektor Perikanan tangkap yang diantaranya adalah ikanÂ Cakalang. Diperlukan adanya upaya untuk menghambat proses pembusukan dengan cara pengawetan dan pengolahan. Pengasapan ikan merupakan penggabungan dari proses penggaraman,pengeringan, dan pemberian asap untuk mencegah kerusakan ikan. Tujuan penelitian iniuntuk mengetahui dan mempelajari mutu dan masa simpan ikanÂ kayu bubuk yang dikemas dengan nitrogen dan tanpa.nitrogen.Metode yang dilakukan untuk uji organoleptik, uji kadar air (AOAC, 2005) dan Angka Lempeng Total (ALT) dengan perlakuan penyimpanan 0 hari, 7 hari dan 14 hari. Berdasarkan hasil penelitian uji organoleptik kenampakan, baud an tekstur dengan nilai rata-rata 7 memenuhi standar SNI. Berdasarkanhasil uji kadar air ikan kayu bubuk yang dikemas plastik dengan nitrogen dan tanpa nitogen mengalami kenaikan kadar air pada masa simpan 0, 7 dan 14 hari dengan nilai tertinggi dengan nilai 13,15 %, produk masih memenuhi standar SNI.Berdasarkan hasil penelitian ALT ikan kayu bubuk yang dikemas plastik dengan nitrogen tidak memenuhi SNI, sedangkan ikan kayu bubuk yang dikemas plastik tanpa nitrogen pada hari ke 0 terlalu sedikit untuk dihitung sedangkan pada hari ke 7 dan 14 tidak memenuhi SNI.